Bone scanning study with Tc-99m-MDP for screening of malignant metastasis in patient with lung carcinoma - Bagaswoto Poedjomartono, Bagaswoto Poedjomartono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1990)
Bone scanning study with Tc-99m-MDP is usually used for screening of malignant metastasis. This method is not invasive, very sensitive but not specific. Indications of bone scanning study are detecting metastasis, evaluation of therapy and follow up the disease. The dosis of Tc-99m-MDP is 15 mCi injected into vena cubiti and after 2-4 hours, scanning will be done. Metastatic lesions are indicated by hyperactive areas on the bone. This scanning is done for evaluation how far the bones are involved in patients with lung carcinoma.Key words: lung carcinoma - bone metastasis - Tc-99m-MDP scanning - radiology - oncology